Microbiological quality of recreational waters in Araraquara, SP, Brazil - Falcão, D. P.; Leite, Clarice Queico Fujimura [UNESP]; Simões, M. J. S.; Mendes-Giannini, Maria José Soares [UNESP]; Valentini, Sandro Roberto [UNESP] (Elsevier B.V., 1993)
The microbiological flora of 108 water samples was explored to evaluate the role of recreational waters as a possible source of human diseases in Araraquara, S.P., Brazil. These waters included six swimming pools and three lakes with beaches. The number of total and fecal coliforms, Escherichia coli, fecal streptococci, Pseudomonas aeruginosa, Staphylococcus aureus, Candida albicans, and heterotrophic organisms was determined. As was the occurrence of Salmonella, Shigella, Yersinia, enteropathogenic E. coli (EPEC), enteroinvasive E. coli (EIEC), Mycobacteria, yeasts in general and dermatophytes. Shigella, Yersinia, EIEC and dermatophytes were not isolated. Other organisms or groups of microorganisms were found in variable proportions. From this study it is concluded that recreational waters used by the population of Araraquara, may be contaminated with potentially pathogenic microorganism and this may serve as a source of human diseases.
Keywords: MICROBIOLOGICAL QUALITY; RECREATIONAL WATERS